Una struttura insediati del Neolitico superiore a S. Andrea di Travo (PC) - Bernabò Brea, M; Cattani, M; Farello, P (Quaderni del Museo Archeologico Etnologico di Modena, 1994)
A rectangular but was excavated at S. Andrea di Travo (PC) on a terrace of the middle valley of the river Trebbia. The hut was broad mt. 15 x 7 and delimitated by continual foundation trench. In this trench traces of numerous pole holes have been identified. Inside the hut there is a small circular hearth and a silos. The archaeological remains date the structure in the late Neolithic Chassey-Lagozza culture, within which can be seen special affinities with the Ligurian and Tuscanian area. The faunal remains show the presence of ovines, pigs and cattle.
Keywords: Val Trebbia, scavo di S. Andrea, capanna